2012
DOI: 10.1074/jbc.m112.390393
|View full text |Cite
|
Sign up to set email alerts
|

The M-T Hook Structure Is Critical for Design of HIV-1 Fusion Inhibitors

Abstract: Background:We recently found that N-terminal residues Met-626 and Thr-627 of HIV-1 fusion inhibitor CP621-652 adopt a unique hook-like structure, termed the M-T hook. Results: The structure and function of the M-T hook have been characterized. Conclusion: The M-T hook is critical for the stability and antiviral activity of HIV-1 fusion inhibitors. Significance: Our data provide important information for designing novel HIV-1 fusion inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(95 citation statements)
references
References 46 publications
5
90
0
Order By: Relevance
“…We recently found that two residues (Met115 and Thr116) preceding the pocketbinding domain (PBD) of CHR peptides adopt a unique M-T hook structure that can greatly enhance the binding and antiviral activities (35)(36)(37)(38)(39). Our crystal structures demonstrated that the residue Thr116 can redirect the peptide chain to position Met115 above the left side of the deep pocket on the trimeric coiled coil of N-terminal helices (NHR) so that its side chain caps the pocket to stabilize the inhibitor binding (37)(38)(39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that two residues (Met115 and Thr116) preceding the pocketbinding domain (PBD) of CHR peptides adopt a unique M-T hook structure that can greatly enhance the binding and antiviral activities (35)(36)(37)(38)(39). Our crystal structures demonstrated that the residue Thr116 can redirect the peptide chain to position Met115 above the left side of the deep pocket on the trimeric coiled coil of N-terminal helices (NHR) so that its side chain caps the pocket to stabilize the inhibitor binding (37)(38)(39).…”
mentioning
confidence: 99%
“…Our crystal structures demonstrated that the residue Thr116 can redirect the peptide chain to position Met115 above the left side of the deep pocket on the trimeric coiled coil of N-terminal helices (NHR) so that its side chain caps the pocket to stabilize the inhibitor binding (37)(38)(39). On the basis of the M-T hook structure, we generated short-peptide fusion inhibitors that mainly targeted the conserved pocket site of gp41 (37,40,41).…”
mentioning
confidence: 99%
“…N peptides, including N36, N36 E49K , N36 L57R , and N36 E49K/L57R , and C peptides, including SC22EK, MTSC22, HP23, C34, C34 N126K , C34 E136G , C34 N126K/E136G , T20, and SFT ( Fig. 1), were synthesized using a standard solid-phase 9-fluorenylmethoxy carbonyl (FMOC) method as described previously (32). All peptides were protected by Nterminal acetylation and C-terminal amidation.…”
Section: Methodsmentioning
confidence: 99%
“…Since its discovery, the deep pocket has been considered an ideal drug target because of its high degree of conservation and essential role in viral entry (23,24); however, inhibitors that specifically target the pocket site often lack a high antiviral activity, most likely due to their weak binding affinity (25)(26)(27)(28)(29)(30). We recently found that two N-terminal residues (Met115 and Thr116) of a C peptide adopt a unique M-T hook structure, in which Thr116 redirects the peptide chain to position Met115 above the left side of the pocket so that its side chain caps the pocket to stabilize the inhibitor binding (31,32). Indeed, the M-T hook structure-modified inhibitors exhibit greatly enhanced binding and inhibitory activities (31)(32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
See 1 more Smart Citation